HTML5 games : creating fun with HTML5, CSS3, and WebGL - Seidelin, Jacob (Chichester, West Sussex, U.K. : John Wiley & Sons, 2012)
"The newest iteration of HTML, HTML5 can be used with JavaScript, CSS3, and WebGL to create beautiful, unique, engaging games that can be played on the web or mobile devices like the iPad or Android phones. Gone are the days where games were only possible with plugin technologies such as Flash and this cutting-edge book shows you how to utilize the latest open web technologies to create a game from scratch using Canvas, HTML5 Audio, WebGL, and WebSockets. You'll discover how to build a framework on which you will create your HTML5 game. Then each successive chapter covers a new aspect of the game, including user input, sound, multiplayer functionality, 2D and 3D graphics, and more."--Publisher's description.
Gaming on the web -- Taking the first steps -- Going mobile -- Building the game -- Delegating tasks to web workers -- Creating graphics with canvas -- Creating the game display -- Interacting with the game -- Animating game graphics -- Creating audio for games -- Creating 3D graphics with WebGL -- Local storage and caching -- Going online with WebSockets -- Resources.
Includes index.
computer bookfair2015
Keywords: Computer games -- Programming; HTML (Document markup language)